Mapping European ecosystem change types in response to land‐use change, extreme climate events, and land degradation. (10th March 2019) - Horion, Stéphanie; Ivits, Eva; De Keersmaecker, Wanda; Tagesson, Torbern; Vogt, Jürgen; Fensholt, Rasmus
Abstract: Extreme climate events and nonsustainable land use are important drivers altering the functioning of European ecosystems, resulting in loss of the services provided. Yet a consensus method for regular continental scale assessment of ecosystem condition in relation to land degradation (LD) is still lacking. Here, we propose a new remote sensing‐based approach allowing for improved, repeated assessment of changing pressure on terrestrial ecosystems. On the basis of segmented trend analysis of water‐use efficiency (WUE), a map of ecosystem change type (ECT) was produced over Europe for the period 1999 to 2013. Results were related to drought and change in land use and land cover and to known cases of soil degradation (LD case‐studies). More than 30% of the European ecosystems experienced significant changes in WUE, of which more than 20% were categorized as abrupt. Large‐scale positive reversals in WUE were observed over regions with increasing crop yield and intensification of wood production, whereas decreased WUE was observed over grassland areas coinciding with high farmland abandonment. Evidence of drought pressure on ecosystem functioning (EF) was observed, with abrupt changes in functioning observed during major European drought events. The ECTs also provided relevant information on the location and type of change in EF over the LD case studies. We conclude that mapping of gradual and abrupt changes in EF is expected to be valuable tool for ecosystem condition assessment that is essential for assessing the success of reaching the LD neutrality objectives set by the United Nations Convention to Combat Desertification.